Prevalence and Model of postpartum blues among Mother with Normal Labor and Cesarean Section: Rachada Phuangprasonka - Phuangprasonka, Rachada; Buala, Onanong; Sittaratasak, Chidchanok (Princess of Naradhiwas University Journal, 2024)
The purpose of this study was to examine the prevalence and pattern of postpartum blues in mothers with normal labor and cesarean sections. 357 samples who experienced postpartum blues after normal labor and cesarean section in the postpartum ward of Samut Prakarn Hospital. The research instruments were a demographic questionnaire and postpartum blues emotion questionnaire of Kennerley and Gath's (1989) which were translated into Thai and then back translated by Phuangprasonka et al. (2016) with a reliability coefficient of 0.79. Data analysis included frequency, percentage, mean, and standard deviation for both demographic data and postpartum blues symptoms. An independent t-test was utilized to compare the postpartum blues score between the groups. Results showed that during the first three days after birth, 43.9% of mothers with normal labor and 58.4% of mothers with cesarean section experienced postpartum blues. The risk of postpartum blues was highest on the first day following delivery and lower in the second - and third-days following delivery in mothers who had normal labor and cesarean section. Between mothers with normal labor and cesarean section, there was a statistically significant difference in the intensity of postpartum blues scores (t = 4.65, p <. 001)